PENERAPAN E-GOVERNMENT KOTA SEMARANG PADA TINGKAT KELURAHAN (STUDI KASUS KELURAHAN PLEBURAN DAN KELURAHAN CANGKIRAN KOTA SEMARANG TAHUN 2019) - Fitrianto, Tito Rizky; Astuti, Puji (Journal of Politic and Government Studies, 2019)
This research was conducted to explain how the application of EGovernmentbetween Kelurahan Pleburan and Kelurahan Cangkiran SemarangCIty in 2019.This study uses a qualitative-descriptive research methodology because this research describes phenomena relating to current and experienced situations, attitudes and views that are present at the moment, the relationship between variables contradicts two or more conditions, the effect on a condition, and the difference between facts. This study is conducted by asking for information to the primary subject, namely the source and the main informant and the secondary subject, as an additional source of data in strengthening the data. The data then explains how the application of E-Government between Kelurahan Pleburan and Kelurahan Cangkiran Semarang City in 2019.The results showed that the application of the E-Government of SemarangCity had been spread evenly at the kelurahan level. Both Kelurahan Pleburanlocated in the downtown area and Kelurahan Cangkiran located in the development area. This can be realized because of the full support of the Semarang CityGovernment both in terms of support, capacity and value. In addition, it also explains the impact of the implementation of E-Government both from the side of the kelurahan itself and the surrounding community.In the future, the Semarang City government needs to increase the numberof Human Resources in the Information Technology field that are placed in eachkelurahan in Semarang City. Establishing cooperation with other parties in making more efficient applications is also needed to improve the performance ofinformation technology-based public services.Keywords: E-Government Implementation, Semarang City, KelurahanPleburan, Kelurahan Cangkiran